UJI AKTIVITAS ANTIPIRETIK EKSTRAK ETANOL BAWANG LANANG HITAM (ALLIUM SATIVUM L.) PADA TIKUS PUTIH JANTAN DENGAN METODE PERKOLASI - Pramesti Listya Agatha, Cindy; Wisnu Kusuma, Eka; Ingrid Anggaraini, Devina (Sekolah Tinggi Ilmu Kesehatan Nasional & Pengurus Cabang Ikatan Apoteker Indonesia (IAI) Sukoharjo, 2023)
Black Onion (Allium Sativum L.) is a species of garlic that is fermented and widely used in food or health. This study aims to determine the black male onion extract antipyretic effectiveness along with to determine the impact of ethanol extract black male onion at dossage of 50mg/KgBb, 100mg/KgBb, 200mg/kgbb on male white rats induced brewer's yeast.. In this study, 25 male white rats were given five treatments: a negative control (CMC-Na), a positive control (Paracetamol 45mg/KgBb), and black onion extract treatment groups with dosages of 50mg/KgBb, 100mg/KgBb, and 200mg/KgBb. Brewer's yeast was administered intraperitoneally. Body temperature is measured rectally with a digital thermometer every 30 minutes for 150 minutes. The data obtained were used to calculate AUC, and the mean data of AUC was analyzed by saphiro wilk test and one-way ANOVA test. Body temperature measurements revealed that an ethanol extract of black onion had the most potent antipyretic effect at a dosage of 100 mg/KgBb